2018
DOI: 10.1111/acel.12755
|View full text |Cite
|
Sign up to set email alerts
|

The genetic component of human longevity: New insights from the analysis of pathway‐based SNPSNP interactions

Abstract: SummaryIn human longevity studies, single nucleotide polymorphism (SNP) analysis identified a large number of genetic variants with small effects, yet not easily replicable in different populations. New insights may come from the combined analysis of different SNPs, especially when grouped by metabolic pathway. We applied this approach to study the joint effect on longevity of SNPs belonging to three candidate pathways, the insulin/insulin‐like growth factor signalling (IIS), DNA repair and pro/antioxidant. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 45 publications
3
28
1
Order By: Relevance
“…In particular the evaluation of heritability is based on an additive model for complex traits that does not consider other inheritance patterns, such as epistasis among others 10 . In literature example of epistatic interactions in longevity exists [11][12][13] . Tan and colleagues 14 analyzing centenarians identified a significant association between the interaction REN gene allele/mitochondrial haplotype H and longevity while the two gene analysed separately showed no significant association.…”
Section: Heritability and Missing Heritability In Longevitymentioning
confidence: 99%
“…In particular the evaluation of heritability is based on an additive model for complex traits that does not consider other inheritance patterns, such as epistasis among others 10 . In literature example of epistatic interactions in longevity exists [11][12][13] . Tan and colleagues 14 analyzing centenarians identified a significant association between the interaction REN gene allele/mitochondrial haplotype H and longevity while the two gene analysed separately showed no significant association.…”
Section: Heritability and Missing Heritability In Longevitymentioning
confidence: 99%
“…Moreover, mortality is increased in individuals with pathologic excess of GH ( Baumann, 1987 ). Studies of the genetic polymorphism of candidate genes, genome-wide association studies (GWAs), and analysis of signaling pathways, genetic networks, and copy number variations, provided evidence that human aging is influenced by genes related to the somatotropic axis ( van Heemst et al, 2005 ; Suh et al, 2008 ; Bonafe and Olivieri, 2009 ; Dato et al, 2018 ) and its downstream targets including FOXO3A ( Blankenburg et al, 2018 ; Revelas et al, 2018 ; Zhao et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…These mutations have been shown to extend life by about 50% in mammals and more in nematodes. In human longevity studies, single nucleotide polymorphism (SNP) analysis identified a large number of genetic variants with metabolic effects [11]. About a hundred of these metabolic manipulations enhance longevity by retarding aging comparable to CR, are not as effective as repair strategies which can reverse aging process.…”
Section: The Genetic Influencementioning
confidence: 99%